2020
DOI: 10.1364/oe.394896
|View full text |Cite
|
Sign up to set email alerts
|

High-energy soliton fission dynamics in multimode GRIN fiber

Abstract: The process of high-energy soliton fission is experimentally and numerically investigated in a graded-index multimode fiber. Fission dynamics is analyzed by comparing numerical observations and simulations. A novel regime is observed, where solitons produced by the fission have a nearly constant Raman wavelength shift and same pulse width over a wide range of soliton energies.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 28 publications
2
33
0
Order By: Relevance
“…This allows for the observation of a host of unexpected nonlinear effects [18,20]. Specifically, the presence of photoluminescence and nonlinear losses, which were ascribed to a MPA mechanism, was recently reported in graded-index (GRIN) MMFs [21,22]. These nonlinear losses introduce a fundamental, and previously undisclosed, nonlinear limitation to the energy transmission capabilities of optical fibers, and may provide an intrinsic limitation for the power scaling of spatiotemporal mode-locking with multimode fiber lasers [23].…”
Section: Introductionmentioning
confidence: 96%
“…This allows for the observation of a host of unexpected nonlinear effects [18,20]. Specifically, the presence of photoluminescence and nonlinear losses, which were ascribed to a MPA mechanism, was recently reported in graded-index (GRIN) MMFs [21,22]. These nonlinear losses introduce a fundamental, and previously undisclosed, nonlinear limitation to the energy transmission capabilities of optical fibers, and may provide an intrinsic limitation for the power scaling of spatiotemporal mode-locking with multimode fiber lasers [23].…”
Section: Introductionmentioning
confidence: 96%
“…Note that the generated multimode solitons feature very high (up to the MW range) peak powers, which permits to drastically improve the quality of the nonlinear imaging of biological samples via two-photon absorption (2PA) and three-photon absorption (3PA), when using infrared light. Because of multimode soliton dynamics and the associated spatiotemporal oscillations induced by selfimaging, dispersive wave generation is obtained, feeding the near-infrared spectrum between 700 nm and 1000 nm [37][38][39]. Additionally, we clearly observed geometric parametric instability (GPI) sidebands, leading to frequency conversion of the input pump into spectral anti-Stokes and Stokes sidebands with large (i.e.…”
Section: Resultsmentioning
confidence: 89%
“…Beyond this wavelength, which represents also the zero-dispersion wavelength (ZDW) of the LP01 mode, a part of the pulse energy propagates in the anomalous dispersion regime, which leads to soliton generation. As well-known, soliton propagation is subject to the Raman-induced soliton self-frequency shift, which leads to spectral broadening towards the 2 microns region [27][28][29][30][36][37][38][39][40]. Note that the generated multimode solitons feature very high (up to the MW range) peak powers, which permits to drastically improve the quality of the nonlinear imaging of biological samples via two-photon absorption (2PA) and three-photon absorption (3PA), when using infrared light.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, we study the nonlinear effects due to the propagation of femtosecond pulses in different lengths of MM fiber with a graded-index (GRIN) core profile (50/125). In particular, for relatively short MM fiber lengths (i.e., 30 cm of GRIN fiber), we revealed a new type of high-energy pulse propagation regime, characterized by the presence of MM solitons, created by the fission of the initial femtosecond pulse [3]. We observed that these solitons have different amplitudes and wavelengths, but nearly equal time duration.…”
Section: Introductionmentioning
confidence: 84%